Wellbeing 2014
DOI: 10.1002/9781118539415.wbwell026
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Health, and Wellbeing in Practice

Abstract: Conventional wisdom in the field of management emphasizes the reduction of stress in the workplace. Although the authors of this chapter recognize the demonstrated destructive nature of negative stress, they argue that the introduction of positive stress has the potential to improve the health and wellbeing for organizations and workers. Five positive pathways through which stress can contribute to building a healthy workplace are explored: strength of character, self‐awareness, power sharing, requisite self‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…This finding confirms the impact of extensive demands on executives’ emotional and psychological wellness ( Quick et al, 2014 ), creating a platform for marital problems. Ostensibly, although interpersonal relationships can be a source of meaning, additional stress and frustration in executives’ marital relationships can become sources of anti-meaning.…”
Section: Research Findingssupporting
confidence: 79%
See 3 more Smart Citations
“…This finding confirms the impact of extensive demands on executives’ emotional and psychological wellness ( Quick et al, 2014 ), creating a platform for marital problems. Ostensibly, although interpersonal relationships can be a source of meaning, additional stress and frustration in executives’ marital relationships can become sources of anti-meaning.…”
Section: Research Findingssupporting
confidence: 79%
“…Spirituality is about a sense of interconnectedness with the universe, being part of something that transcends the self ( Weeks and Schaffert, 2019 ), and a sense of purpose and meaning ( Quick et al, 2014 ; Van der Walt and De Klerk, 2015 ). Self-transcendence is an integral element of meaning and spiritual well-being ( Worth and Smith, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, several studies have demonstrated that some can experience benefits from stressful experiences (Schneiderman et al, 2005). Specifically, stress was linked to positive outcomes like personal initiative (Fay & Sonnentag, 2002) and health (Quick et al, 2014). Accordingly, a stress belief started to receive attention as a factor that changes the influences of stress.…”
Section: Introductionmentioning
confidence: 99%